Electrolytic capacitor
By forming a carbon layer on the surface of the cathode foil of the electrolytic capacitor, and using nitro compounds to efficiently receive electrons and absorb hydrogen ions in the end surface area of the cathode foil, the problem of severe hydrogen generation in the medium and high-voltage electrolytic capacitor is solved, and the thinning of the dielectric oxidation coating and the stability of the capacitor are achieved.
Patent Information
- Application Number
- CN202380053441.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-13
- Filing Date
- 2023-06-26
- Publication Date
- 2025-02-28
AI Technical Summary
In electrolytic capacitors for medium and high voltage use greater than or equal to 160V, in order to maintain the withstand voltage, the dielectric oxidation coating needs to be thinned, resulting in increased leakage current and intense hydrogen generation, affecting the stability of the capacitor.
By forming a carbon layer on the surface of the cathode foil as a reduction site, the nitro compound can efficiently receive electrons and absorb hydrogen ions in the end surface area of the cathode foil, block the hydrogen generation path, and form close contacts between the carbon layer and the cathode foil to improve the reduction reaction efficiency of the nitro compound.
It effectively suppresses the amount of hydrogen generated in the electrolytic capacitor, prevents the decrease of the electrostatic capacitance, and improves the stability and durability of the capacitor.
Smart Images

Figure CN119547171A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to electrolytic capacitors. Background Art
[0002] The electrolytic capacitor is formed by placing an anode foil having a dielectric oxide film formed on a valve metal foil such as tantalum or aluminum and a cathode foil made of the same type or other metal foil opposite to each other. The anode foil and the cathode foil are connected to the lead terminals by seam welding, cold welding, ultrasonic welding, laser welding, etc. The paired anode foil and cathode foil are stored in an outer casing, which is sealed by a sealing body. The lead terminals are led out from the sealing body.
[0003] An electrolyte is filled between the anode foil and the cathode foil. The electrolyte is interposed between the anode foil and the cathode foil and is in close contact with the concave and convex surface of the anode foil, acting as a true cathode. The electrolyte repairs the deteriorated, damaged, etc., parts of the dielectric oxide film formed on the anode foil through leakage current. However, hydrogen gas is generated when the film repair of the dielectric oxide film by leakage current begins.
[0004] That is, when the film is repaired by leakage current on the anode side, a positive electrode reaction represented by the following chemical reaction formula (1) occurs. Moreover, when the film is repaired by leakage current on the cathode side, electrons generated by the positive electrode reaction are received, and a negative electrode reaction represented by the following chemical reaction formula (2) occurs by reducing hydrogen ions. The atomic hydrogen generated in the chemical reaction formula (2) combines as represented by the following chemical reaction formula (3) to generate hydrogen gas.
[0005] 2Al+3H2O→Al2O3+6H + +6e - …(1)
[0006] 6H + +6e - →6H ad …(2)
[0007] 6H ad →3H2…(3)
[0008] The generation of hydrogen gas will increase the internal pressure of the electrolytic capacitor, causing the shell and the sealing body that accommodate the capacitor element to expand. In the worst case, there is a concern that the increase in the internal pressure of the electrolytic capacitor caused by hydrogen gas may cause the pressure relief valve provided in the electrolytic capacitor to open or cause leakage. Therefore, nitro compounds are sometimes added to the electrolyte to suppress the generation of hydrogen gas (for example, refer to Patent Document 1).
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 4-10512 Summary of the invention
[0010] Here, the electrolytic capacitor can be considered as a series capacitor synthesized by connecting the electrostatic capacitance of the anode foil and the electrostatic capacitance of the cathode in series. When the electrostatic capacitance of the cathode foil is sufficiently larger than the electrostatic capacitance of the anode foil, if the effective area of the surface of the anode foil facing the cathode foil is set to S[m 2 ], the thickness of the dielectric oxide film formed on the surface of the anode foil is d[m], the relative dielectric constant of the dielectric oxide film is ε, and the dielectric constant of vacuum is 8.854×10 -12 [F / m], the electrostatic capacitance C[F] of the electrolytic capacitor can be approximated by the following formula 1.
[0011] (Formula 1)
[0012] C = 8.854 × 10 -12 ×ε·S / d
[0013] Moreover, sometimes, for on-board applications such as electric vehicles and power applications, the electrolytic capacitor is required to have a withstand voltage greater than or equal to 160V. The thickness d of the dielectric oxide film of the anode foil has a great influence on the withstand voltage of the electrolytic capacitor. Therefore, an electrolytic capacitor that can withstand medium and high voltages greater than or equal to 160V needs to have a thick dielectric oxide film. However, thickening the dielectric oxide film will increase the thickness d of formula 1, so the electrostatic capacitance C will decrease. Therefore, the electrolytic capacitor for medium and high voltage applications greater than or equal to 160V has an expansion layer composed of many tunnel-shaped pits in the anode foil. In addition, the electrolytic capacitor has an expansion layer in the anode foil, and the expansion layer has tunnel-shaped pits that penetrate the foil locally or over the entire surface.
[0014] As mentioned above, through the surface expansion technology, the thickness of the dielectric oxide film is ensured for electrolytic capacitors for medium and high voltage applications greater than or equal to 160V, and the surface area of the anode foil is increased. However, in recent years, electrolytic capacitors for medium and high voltage applications greater than or equal to 160V have been required to have a higher electrostatic capacitance. In other words, while maintaining the withstand voltage, it is also necessary to study the thinning of the dielectric oxide film.
[0015] However, if the dielectric oxide film is continuously thinned, the withstand voltage of the anode foil will decrease and the leakage current will increase in accordance with the reduction in the thickness of the dielectric oxide film. As the leakage current on the anode side increases, the movement of charges and the generation of hydrogen ions in the electrode surface on the anode side become intense. Therefore, in electrolytic capacitors for medium and high voltage applications of 160V or more, in order to maintain the withstand voltage and continuously thin the dielectric oxide film, it is necessary to continuously and more efficiently give the nitro compound added to the electrolyte the opportunity to suppress the reaction of hydrogen.
[0016] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an electrolytic capacitor that uses a nitro compound efficiently and suppresses the total amount of gas generated in the electrolytic capacitor.
[0017] The inventors of the present invention have conducted diligent research and have confirmed that the nitro compound mainly causes the hydrogen gas inhibition reaction at the end face of the cathode foil. Here, the cathode foil is cut to an industrially desired width and installed in an electrolytic capacitor. A dielectric oxide film is formed on the surface of the cathode foil, but there is no dielectric oxide film at the end face exposed by cutting, or although an oxide film is formed, the oxide film is extremely thin. Therefore, the nitro compound accepts and donates electrons generated by the chemical reaction formula (1) at the end face region of the cathode foil, and also absorbs hydrogen ions, thereby inhibiting the generation of atomic hydrogen and the generation of hydrogen gas.
[0018] Thus, a reduction site that is difficult to be naturally oxidized is formed on the surface of the cathode foil. By making the reduction site electrically conductive with the cathode foil, the generation of hydrogen can be more efficiently suppressed. That is, the nitro compound also receives electrons from the site and absorbs hydrogen ions at the site. Moreover, the nitro compound prevents chemical reaction formulas (2) and (3), further suppressing the generation of hydrogen.
[0019] However, the nitro compound is reduced on the cathode side and absorbs hydrogen ions as shown in the following reaction formula (4). As a result, atomic hydrogen is generated from hydrogen ions, and the reaction paths of reaction formulas (2) and (3) in which atomic hydrogen is converted into hydrogen gas are blocked, thereby suppressing the generation of hydrogen gas. Through this reaction formula (4), a reduction product (hereinafter referred to as a reduction product) generated by the reduction of a nitro compound such as aniline is generated starting from the nitro compound.
[0020]
[0021] When the reduction site increases the chance of the nitro compound's reduction reaction and the amount of the nitro compound added increases, the amount of the reduction product generated increases significantly, reducing the electrostatic capacitance of the electrolytic capacitor. On the other hand, when the cathode body is formed with reduction sites, the nitro compound is used efficiently, so that even if the amount of the nitro compound added is small, the generation of hydrogen can be suppressed for a long period of time.
[0022] The present invention is completed based on the above-mentioned insights. In order to solve the above-mentioned problems, an electrolytic capacitor comprises: an anode foil, which is formed with a dielectric oxide film; a cathode body, which has reduction sites on its surface; and an electrolyte, which is between the anode foil and the cathode body and contains a nitro compound, wherein the cathode body comprises: a cathode foil, which is composed of a valve metal; and a carbon layer, which is stacked on the cathode foil and serves as the reduction site, wherein the nitro compound is present at a rate of 100% per 1 cm of the cathode body. 2A proportion of the projected area less than or equal to 1.5 mg is contained in the electrolyte.
[0023] Regarding the formation of the carbon layer, the capacitance appearance ratio is first defined. The capacitance appearance ratio is the ratio of the electrostatic capacitance of the electrolytic capacitor to the electrostatic capacitance on the anode side. That is, the capacitance appearance ratio is considered to be the percentage of the ratio obtained by dividing the synthetic electrostatic capacitance of the electrolytic capacitor as a capacitor formed by connecting the anode side and the cathode side in series by the electrostatic capacitance on the anode side. The synthetic electrostatic capacitance is the value obtained by dividing the multiplication result of the electrostatic capacitance on the anode side and the electrostatic capacitance on the cathode side by the sum of the electrostatic capacitance on the anode side and the electrostatic capacitance on the cathode side. Therefore, the capacitance appearance ratio is expressed by the following formula 2.
[0024] (Formula 2)
[0025]
[0026] As shown in Formula 2, when the electrostatic capacitance on the anode side is large, the influence of the cathode side on the capacitance appearance ratio becomes large. On the other hand, when the electrostatic capacitance on the anode side is small, the influence of the cathode side on the capacitance appearance ratio becomes small.
[0027] In the field of electrolytic capacitors, the anode foil for electrolytic capacitors for so-called medium and high voltage applications greater than or equal to 160V has a smaller electrostatic capacitance per unit area than the anode foil for electrolytic capacitors for low voltage applications. In addition, in electrolytic capacitors for so-called medium and high voltage applications greater than or equal to 160V, the difference in electrostatic capacitance between the anode side and the cathode side is large. The reason for this is that in the anode foil for electrolytic capacitors for medium and high voltage applications, in order to ensure the withstand voltage, the dielectric oxide coating on the surface of the expanded layer becomes thicker. If the capacitance appearance ratio is improved from the point of view of considering, in the electrolytic capacitors in the low-voltage area where the electrostatic capacitance on the anode side is large, in order to increase the capacitance appearance ratio, the effect of increasing the capacitance on the cathode side is large. However, for electrolytic capacitors for medium and high voltage applications with small electrostatic capacitance on the anode side, or electrolytic capacitors with an electrostatic capacitance on the cathode side that is one order of magnitude larger than that on the anode side, even if the electrostatic capacitance on the cathode side is increased, the effect of increasing the capacitance appearance ratio is small.
[0028] For example, in electrolytic capacitors for low voltage applications, 2 In the case of an anode foil with a capacitance of 10 μF, 2 When the capacitance of the cathode foil is 100μF, the capacitance ratio becomes 90.9%. However, when the cathode foil is 1cm thick, 2 The capacitance appearance ratio of the electrostatic capacitor is 99.0% when the capacitance is set to 1000μF, and the capacitance appearance ratio is expected to increase by 109%. On the other hand, as an electrolytic capacitor for medium and high voltage applications, the capacitance appearance ratio of the electrolytic capacitor is 99.0% when the capacitance is set to 1000μF, and the capacitance appearance ratio is expected to increase by 109%. 2The electrostatic capacitance of the anode foil is 1μF, and the 2 When the capacitance of the cathode foil is 100 μF, the capacitance ratio becomes 99.0%. However, when the cathode foil is 1 cm thick, 2 When the electrostatic capacitance is set to 1000 μF, the capacitance appearance ratio is 99.9%, and the capacitance appearance ratio is hardly improved.
[0029] In electrolytic capacitors for medium and high voltage applications, the effect of the capacitance appearance ratio is small even if the electrostatic capacitance on the cathode side is increased. Considering the increase in the number of processes caused by the use of carbon materials, it is not advisable to increase the capacitance of the cathode foil. However, based on the knowledge of the inventors, the carbon layer can be redefined as a reduction site, and the electrolytic capacitor as described above can be realized.
[0030] The cathode foil may have a cathode side expansion portion on its surface, and the carbon layer may be formed on the cathode side expansion portion.
[0031] The carbon layer and the cathode-side expanded portion may be crimped.
[0032] The carbon layer may enter into the cathode side expansion portion.
[0033] The cathode-side expanded portion may have sponge-like pits, the carbon layer may contain a carbon material, and the carbon material of the carbon layer may enter the sponge-like pits.
[0034] In addition, the anode foil may include: an expanded portion formed on the foil surface; and a dielectric oxide film formed on the surface of the expanded portion, with a thickness greater than or equal to 200 nm. The anode foil may have a dielectric constant less than or equal to 3.5 μF / cm 2 Electrostatic capacitor. It can be used for medium and high voltage applications greater than or equal to 160V.
[0035] Effects of the Invention
[0036] According to the present invention, the amount of gas generated in the electrolytic capacitor can be suppressed, and a decrease in the electrostatic capacitance of the electrolytic capacitor can be prevented. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Graphs showing temporal changes in the volumes of the electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 to 4.
[0038] Figure 2 It is a graph showing the volumes of the electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 to 4 in units of accumulated electricity.
[0039] Figure 3 It is a graph showing the time change of the capacitance of Examples 1 and 2 and Comparative Examples 1 and 3.
[0040] Figure 4 It is a graph showing the capacitance of Examples 1 and 2 and Comparative Examples 1 and 3 in units of accumulated electricity. DETAILED DESCRIPTION
[0041] (Electrolytic Capacitors)
[0042] The electrode body involved in the embodiment of the present invention and the electrolytic capacitor using the electrode body as the cathode are described. The electrolytic capacitor is a passive element that stores and discharges electric charges corresponding to the electrostatic capacitance. The electrolytic capacitor has a winding type or a stacked type capacitor element. The capacitor element is formed by making an anode foil having a dielectric oxide film formed on the surface and a cathode body composed of a foil of the same type as the anode foil or other metals face each other through a partition and impregnated with an electrolyte. In addition, the electrolyte can also be solidified into a gel state.
[0043] (Cathode)
[0044] The cathode body is a laminated body in which a carbon layer containing a carbon material is laminated on the surface of a cathode foil formed by extending a valve metal as a current collector. The carbon layer is less likely to form a passivation film than the valve metal of the cathode foil. The carbon layer serves as a reduction site that donates electrons to the nitro compound.
[0045] Examples of the valve metal include aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony, and the purity is preferably about 99% or more.
[0046] Examples of carbon materials contained in the carbon layer include activated carbon, graphite, carbon black, carbon nanohorns, or fibrous carbon. Activated carbon is made from natural plant tissues such as coconut shells, synthetic resins such as phenol, coal, coke, asphalt, and other fossil fuels. Examples of graphite include natural graphite, artificial graphite, and graphitized Ketjen black. Examples of carbon black include Ketjen black, acetylene black, channel black, and thermal black. Examples of fibrous carbon include carbon nanotubes (hereinafter referred to as CNTs), carbon nanofibers (hereinafter referred to as CNFs), and the like.
[0047] As a method for forming a carbon layer on the cathode foil, vacuum evaporation, sputtering, ion plating, CVD, coating, electrolysis, electroless plating, etc. are cited. In the case of coating, the carbon material is dispersed in a dispersion solvent to prepare a slurry, and the slurry is applied and dried on the cathode foil by a slurry casting method, a doctor blade method, or a spray spray method. In the case of evaporation, the carbon material is evaporated by heating it with electricity in a vacuum, or an electron beam is impacted on the carbon material in a vacuum to evaporate it, and a film of the carbon material is formed on the cathode foil. In addition, in the case of sputtering, a target material composed of a carbon material and a cathode foil are arranged in a vacuum container, an inert gas is introduced into the vacuum container, and a voltage is applied, thereby causing the plasmatized inert gas to collide with the target material, and the particles of the carbon material impacted from the target material are deposited on the cathode foil.
[0048] In addition, a natural oxide film or a chemical film may be formed outside the carbon layer. The natural oxide film is formed by the cathode foil reacting with oxygen in the air, and the chemical film is an oxide film intentionally formed by applying a voltage to a solution without halogen ions such as an aqueous solution of adipic acid, boric acid, phosphoric acid, etc. When the valve metal is aluminum, the oxide film is aluminum oxide.
[0049] However, in the case where the cathode body is a laminate of a cathode foil and a carbon layer, it is preferred that the carbon layer is in close contact with the cathode foil, the natural oxide film and the chemical film are destroyed, or the natural oxide film and the chemical film are set to a thickness that causes a tunnel effect so that the valve metal and the carbon layer are connected. If these films are broken through by the carbon material of the carbon layer, the carbon layer can easily be electrically connected to the unoxidized metal part of the cathode foil, and it is easy to become a good reduction site, and efficiently transfer electrons to the nitro compound.
[0050] In order to improve the adhesion between the carbon layer and the cathode foil, it is preferred to perform a stamping process on the cathode body composed of the carbon layer and the cathode foil. During the stamping process, for example, the cathode body composed of the carbon layer and the cathode foil is clamped by a pressure roller and a stamping line pressure is applied. The stamping pressure is preferably 0.01 to 100 t / cm 2 The natural oxide film and chemical film can be easily broken through by stamping.
[0051] In addition, a surface expansion layer may be formed on the surface of the cathode foil to expand the surface area of the cathode body. The surface expansion layer is formed by electrolytic etching, chemical etching, sandblasting, etc., or by evaporating or sintering metal particles on the foil body. As an example of electrolytic etching, AC etching is cited. In the AC etching process, the cathode foil is immersed in an acidic aqueous solution such as hydrochloric acid in which halogen ions exist, so that an alternating current flows. In addition, in chemical etching, the metal foil is immersed in an acid solution or an alkaline solution. That is, the surface expansion layer refers to the formation area of the sponge-like etching pits, or the area of the porous structure composed of the gaps between dense powders. In addition, even if the etching pits are tunnel-shaped pits formed by DC etching, they can also be formed into tunnel-shaped pits that penetrate the cathode foil.
[0052] When the surface area of the cathode body is enlarged by forming the surface expansion layer, the number and thickness of the conductive paths between the reduction sites and the cathode foil increase, and the conductive paths are brought into close contact, thereby increasing the chances of the reduction reaction of the nitro compound and suppressing the generation of hydrogen.
[0053] In addition, if the surface expansion layer is formed, the cathode foil and the carbon layer are more likely to be in close contact. That is, the carbon material enters the concavo-convex of the surface expansion layer, thereby improving the close contact between the carbon layer and the cathode foil. If a stamping process is performed on the basis of the formation of the surface expansion layer, the carbon material can be pressed into the pores of the surface expansion layer, and the carbon material can be deformed along the concavo-convex surface of the surface expansion layer, and the close contact and fixability of the carbon layer and the cathode body are further improved.
[0054] When forming a surface expansion layer, carbon black as spherical carbon is particularly preferred as the carbon material contained in the carbon layer. When the surface expansion layer formed on the surface of the cathode foil is an etching pit, by using carbon black with a particle diameter smaller than the opening diameter of the etching pit, it is easy to enter the deeper part of the etching pit, and the carbon layer is in close contact with the cathode foil.
[0055] However, the carbon layer may contain a mixture of two or more of these carbon materials. For example, the carbon material contained in the carbon layer is preferably flaky or scale-like graphite and carbon black as spherical carbon. The flaky or scale-like graphite is preferably in the range of 1:5 to 1:100 in terms of the aspect ratio of the short diameter to the long diameter. The carbon black as spherical carbon preferably has an average primary particle diameter of less than or equal to 100 nm. When a carbon layer containing the carbon material of this combination is stacked on the cathode foil, the carbon black is easily rubbed into the pores of the expanded layer through the graphite. Graphite is easily deformed along the concave and convex surface of the expanded layer and is easily stacked on the concave and convex surface. Moreover, the graphite becomes a pressing cover to press the spherical carbon rubbed into the pores. Therefore, the adhesion and fixability of the carbon layer and the cathode foil are further improved.
[0056] In addition, activated carbon and fibrous carbon have delocalized electrons and a large specific surface area, so they can be added to the carbon layer together with carbon black as spherical carbon, or together with a mixture of flaky or scale-like graphite and carbon black as spherical carbon.
[0057] (Anode Foil)
[0058] The anode foil is a long strip of foil made of valve metal. The purity of the anode foil is preferably greater than or equal to about 99.9%. The anode foil is formed by forming an expansion layer on an extended foil and forming a dielectric oxide coating on the surface of the expansion layer. The expansion layer corresponds to medium and high voltage applications greater than or equal to 160V, and has a plurality of tunnel-shaped pits sunk from the foil surface in the thickness direction through DC etching. In order to cope with high capacity, the tunnel-shaped pits can be formed to penetrate the anode foil. Alternatively, the expansion layer is formed by sintering a powder of the valve metal, or by vapor-depositing a coating of metal particles or the like on the foil and applying a coating.
[0059] The dielectric oxide film forming the anode foil is typically an oxide film formed on the surface layer of the anode foil, and if the anode foil is made of aluminum, it is an aluminum oxide layer obtained by oxidizing the porous structure region. The dielectric oxide film is formed by a chemical conversion treatment in which a voltage is applied in a solution without halogen ions such as an acid such as ammonium borate, ammonium phosphate, ammonium adipate, or an aqueous solution of these acids.
[0060] The dielectric oxide film is preferably set to 3.5 μF / cm or less for medium and high voltage applications. 2 If the capacitance generated on the anode side exceeds 3.5μF / cm 2 If the anode side electrostatic capacitance is reduced, the dielectric oxide film becomes thinner and the withstand voltage is reduced. In addition, the dielectric oxide film has a thickness of greater than or equal to 200nm, which can also contribute to the withstand voltage of the electrolytic capacitor for medium and high voltage applications greater than or equal to 160V.
[0061] (Electrolyte)
[0062] The electrolyte is a mixed solution in which a solute is dissolved relative to a solvent and an additive is added as needed. The solvent is preferably ethylene glycol. If ethylene glycol is used as a solvent, the withstand voltage of the electrolytic capacitor is improved, and it is suitable for medium and high voltage applications greater than or equal to 160V. However, if the required withstand voltage can be obtained by expanding the surface of the anode foil and forming the anode foil, the solvent can be any of a protic polar solvent or an aprotic polar solvent. As protic organic polar solvents, monohydric alcohols and polyhydric alcohols, oxyalcohol compounds, etc. are representatively cited. As aprotic organic polar solvents, sulfones, amides, lactones, cyclic amides, nitriles, oxides, etc. are representatively cited.
[0063] The solute contained in the electrolyte includes components of anions and cations, and is typically an organic acid or a salt thereof, an inorganic acid or a salt thereof, or a composite compound of an organic acid and an inorganic acid, or a salt having ion dissociation thereof, which may be used alone or in combination of two or more. The acid that will become an anion and the salt base that will become a cation may be added to the electrolyte as solute components.
[0064] A nitro compound is added to the electrolyte solution, which absorbs hydrogen ions by sending and receiving electrons at the reduction site of the cathode body. Examples of the nitro compound include o-nitrobenzyl alcohol, p-nitrobenzyl alcohol, m-nitrobenzyl alcohol, o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, and nitrobenzene.
[0065] Nitro compounds are present in 1 cm2 of the cathode body. 2 The projected area is less than or equal to 1.5 mg. The reduction sites such as the carbon layer are formed on the cathode foil, so the chance of reduction reaction of the nitro compound increases. Therefore, if the amount of nitro compound added increases, the reduction product of the nitro compound will also increase. However, if the amount of nitro compound added is 100 mg per 1 cm of the cathode body, the reduction product of the nitro compound will also increase. 2 When the projected area is less than or equal to 1.5 mg, the amount of reduction product generated is within the allowable range and does not hinder the discovery of the electrostatic capacitance of the electrolytic capacitor.
[0066] In addition, other additives can be added to the electrolyte. As additives, polyethylene glycol, complexes of boric acid and polysaccharides (mannitol, sorbitol, etc.), complexes of boric acid and polyols, boric acid esters, nitro compounds, phosphates, etc. can be cited. They can be used alone or in combination of two or more.
[0067] (Partition)
[0068] The separator is interposed between the anode foil and the cathode body to prevent short circuit between the anode foil and the cathode body, and retains the electrolyte. Examples of the separator include kraft paper, Manila hemp, esparto, hemp, rayon and other cellulose and mixed papers thereof, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate and their derivatives, polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins, aliphatic polyamides, semi-aromatic polyamides, wholly aromatic polyamides and other polyamide resins, polyimide resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins and the like, and these resins can be used alone or in combination, and can also be used in combination with cellulose.
[0069] (Example)
[0070] Hereinafter, the present invention will be described in more detail based on examples. In addition, the present invention is not limited to the following examples.
[0071] (Example 1)
[0072] An electrolytic capacitor of Example 1 for high voltage use with a rated voltage of 225V was produced. A 3cm×4cm aluminum foil was used as the cathode foil. The aluminum foil was subjected to an AC etching treatment to form an expanded surface layer consisting of sponge-like etching pits on both sides of the foil. In the AC etching treatment, the cathode foil was immersed in an acidic aqueous solution with a liquid temperature of 25°C and approximately 8% by weight of hydrochloric acid as the main electrolyte, and an AC current of 10Hz and a current density of 0.14A / cm 2 A current of 10000 W was applied to the substrate for about 5 minutes to expand the two sides of the aluminum foil. Next, the aluminum foil was subjected to a chemical conversion treatment to form a dielectric oxide film on the surface of the expanded layer. In the chemical conversion treatment, after removing the chlorine gas attached during the AC etching treatment in a phosphoric acid aqueous solution, a voltage was applied in an aqueous solution of ammonium dihydrogen phosphate.
[0073] A carbon layer is stacked on the cathode foil. The carbon layer contains carbon black as a carbon material. Specifically, carbon black powder, styrene butadiene rubber (SBR) as a binder, and a sodium carboxymethyl cellulose (CMC-Na) aqueous solution as a dispersant aqueous solution are mixed and kneaded to prepare a slurry.
[0074] The slurry is evenly applied to the cathode foil. After the slurry is heated and dried to volatilize the solvent, the cathode body is subjected to a stamping process. During the stamping process, the cathode body is sandwiched by a pressure roller, and a stamping line pressure of 5.38 kN / cm is applied to fix the carbon layer on the cathode foil. The stamping line pressure is applied using a stamping machine manufactured by Takumi Technology Co., Ltd. The diameter of the pressure roller is 180 mm, the stamping process width is 130 mm, and the cathode body is transported once at 3 m / min.
[0075] In addition, a 3 cm × 4 cm aluminum foil was used as the anode foil. The aluminum foil was subjected to a direct current etching process to form an expanded surface layer consisting of tunnel-shaped etching pits. In the direct current etching process, a first process of forming pits and a second process of expanding pits were used. In the first process, the aluminum foil was electrochemically etched by a direct current in an aqueous solution containing chloride ions. In the second process, in order to expand the pits formed in the aluminum foil after the first process, a direct current was electrochemically etched in an aqueous solution containing nitric acid ions.
[0076] After the surface expansion layer was formed, the anode foil was subjected to a chemical conversion treatment to form a dielectric oxide film on the surface of the surface expansion layer. Specifically, a voltage of 286 V was applied in a chemical conversion solution of 70 wt % boric acid at a liquid temperature of 85°C.
[0077] The anode foil and the cathode body are connected to the lead terminals of the aluminum ear piece by ultrasonic wave. In addition, a laminated body is produced in which the anode foil is sandwiched between two cathode bodies with a separator inserted. As a separator, a 4 cm × 5 cm kraft paper-like separator is used. In addition, before stacking, the back side of the cathode body opposite to the surface facing the anode foil through the separator is covered with an insulating resin.
[0078] The stack of the anode foil, cathode body and separator is impregnated with an electrolyte. The electrolyte contains ethylene glycol as a solvent and azelate as a solute. In addition, p-nitrobenzyl alcohol is added to the electrolyte as a nitro compound in an amount of 0.4 wt % relative to the total amount of the electrolyte. The amount of the nitro compound added is equivalent to 10% by weight of the cathode body per 1 cm 2 Projected area: 0.7 mg / cm 2 .
[0079] After the electrolyte is impregnated, the stack of anode foil, cathode body and separator is packaged by a laminating material. The lead terminals connected to the cathode foil and cathode body are led out of the laminating material. Thus, an electrolytic capacitor of a laminated battery is produced. As a laminating material, aluminum with a thickness of 110 μm is used. After the laminated battery is produced, an aging treatment is performed. The aging treatment is to apply a voltage of 230V for 60 minutes at room temperature (30°C). Thus, the electrolytic capacitor involved in Example 1 with a rated voltage of 225V is produced.
[0080] (Example 2)
[0081] An electrolytic capacitor of Example 2 was also produced. In the electrolytic capacitor of Example 2, p-nitrobenzyl alcohol was added as a nitro compound to the electrolyte in an amount of 0.8 wt % relative to the total amount of the electrolyte. The amount of the nitro compound added was equivalent to 0.8 wt % per 1 cm of the cathode body. 2 Projected area: 1.5 mg / cm 2 The electrolytic capacitor of Example 2 was produced by the same method and conditions as those of Example 1 except for the above, including the components of the carbon layer formed on the cathode foil.
[0082] (Comparative Example 1)
[0083] An electrolytic capacitor of Comparative Example 1 was also prepared. In the electrolytic capacitor of Comparative Example 1, p-nitrobenzyl alcohol was added as a nitro compound to the electrolyte in an amount of 1.2 wt % relative to the total amount of the electrolyte. The amount of the nitro compound added was equivalent to 1.2 wt % per 1 cm of the cathode body. 2 Projected area: 2.2 mg / cm 2 The electrolytic capacitor of Comparative Example 1 was produced by the same method and conditions as those of Example 1 except for the above, including the components of the carbon layer formed on the cathode foil.
[0084] (Comparative Example 2)
[0085] An electrolytic capacitor of Comparative Example 2 was also produced. In the electrolytic capacitor of Comparative Example 2, a cathode foil formed by extending an aluminum foil was used as the cathode body. The purity of the aluminum foil was greater than or equal to 99.9%, and there was no laminate such as a carbon layer on the surface of the aluminum foil. In the electrolyte, as in Example 2, p-nitrobenzyl alcohol was added as a nitro compound in an amount of 0.8% by weight relative to the total amount of the electrolyte. The amount of the nitro compound added was the same as in Example 2, corresponding to 1 cm2 of the cathode body. 2 Projected area: 1.5 mg / cm 2 Regarding other aspects, the electrolytic capacitor of Comparative Example 2 contained a nitro compound and the like in the electrolyte solution and was produced by the same method and under the same conditions as in Example 1.
[0086] (Comparative Example 3)
[0087] An electrolytic capacitor of Comparative Example 3 was also produced. In the electrolytic capacitor of Comparative Example 3, a cathode foil formed by extending an aluminum foil was used as a cathode body. The purity of the aluminum foil was greater than or equal to 99.9%, and there was no laminate such as a carbon layer on the surface of the aluminum foil. In the electrolyte, p-nitrobenzyl alcohol was added as a nitro compound in an amount of 1.6 wt % relative to the total amount of the electrolyte. The amount of the nitro compound added was equivalent to 1.6 wt % for every 1 cm of the cathode body. 2 Projected area: 3.0 mg / cm 2 Regarding other aspects, the electrolytic capacitor of Comparative Example 3 contained a nitro compound and the like in the electrolyte solution and was produced by the same method and under the same conditions as in Example 1.
[0088] (Comparative Example 4)
[0089] An electrolytic capacitor of Comparative Example 4 was also produced. In the electrolytic capacitor of Comparative Example 4, a cathode foil formed by extending an aluminum foil was used as a cathode body. The purity of the aluminum foil was greater than or equal to 99.9%, and there was no laminate such as a carbon layer on the surface of the aluminum foil. No nitro compound was added to the electrolyte.
[0090] (Gas generation measurement test)
[0091] The amount of gas generated by the electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 to 4 was measured. A high voltage of DC225V was continuously applied to each electrolytic capacitor at a temperature of 105°C, and the amount of gas generated at each time was measured. The amount of gas generated was measured by the amount of expansion (volume change; ml) of the laminated battery. The amount of expansion of the laminated battery was measured by the Archimedean method. That is, by measuring the weight increase when the laminated battery is immersed in water, the volume of the liquid discharged by the laminated battery is measured.
[0092] In addition, the cumulative amount of leakage current (C) is measured when measuring the amount of gas generated. In order to measure the cumulative amount of electricity, a 100kΩ resistor is connected in series with the electrolytic capacitor, and the voltage value to which the resistor is subjected is measured periodically when the voltage is applied. The leakage current is calculated by dividing the voltage value by the resistance value. In addition, the cumulative amount of electricity (C) at the time of the Nth measurement is calculated by multiplying the sum of the leakage currents up to the Nth measurement in the measurement sequence by the time interval of the voltage value measurement.
[0093] The relationship between gas generation and elapsed time is Figure 1 In addition, the relationship between the amount of gas generated and the accumulated electricity is shown in Figure 2 Shown. Figure 1 Graphs showing temporal changes in the volumes of the electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 to 4. Figure 2 It is a graph showing the volumes of the electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 to 4 in units of accumulated electricity.
[0094] like Figure 1 As shown, the expansion of the electrolytic capacitor of Comparative Example 3 began 258 hours after the start of the measurement of the amount of gas generated, and became rapid after 570 hours. Figure 1 As shown, the expansion of the electrolytic capacitors of Examples 1 and 2 and Comparative Example 1 did not start after 570 hours from the start of the measurement of the amount of gas generated, but started after 1026 hours, but the change was stable.
[0095] like Figure 2 As shown, the expansion of the electrolytic capacitor of Comparative Example 3 is when the cumulative amount of leakage current reaches 1.2C / cm 2 On the other hand, the electrolytic capacitor of Example 1 is 2 The electrolytic capacitor of Example 2 is used when the cumulative leakage current reaches 2.4C / cm 2 The electrolytic capacitor of Comparative Example 1 is when the cumulative amount of leakage current reaches 2.8C / cm 2Then start.
[0096] The expansion of the electrolytic capacitor is caused by the generation of hydrogen. Therefore, the cumulative amount of electricity when the expansion of the electrolytic capacitor becomes rapid can be said to be the cumulative amount of electricity when hydrogen begins to be generated. Therefore, in Examples 1 and 2 and Comparative Example 1, the generation of hydrogen is suppressed by the reduction reaction of the nitro compound at the beginning of the test when the voltage is applied, but as the test time passes, the nitro compound disappears at the time of the cumulative amount of electricity when the expansion of the electrolytic capacitor becomes rapid, and it can be inferred that hydrogen has been generated. That is, it can be said that the following suggestion is given, that is, the cumulative amount of electricity when the expansion of the electrolytic capacitor becomes rapid is the cumulative amount of electricity when the nitro compound disappears, and the cumulative amount of electricity consumed by the nitro compound is different depending on the amount of nitro compound added.
[0097] Here, in the electrolytic capacitor of Comparative Example 3, the nitro compound is present in an amount of 1 cm2 per cathode body. 2 Projected area: 3.0 mg / cm 2 In contrast, in the electrolytic capacitors of Examples 1 and 2 and Comparative Example 1, the nitro compound was added to the electrolyte at a maximum of 1 cm2 per 1 cm2 of the cathode body. 2 Projected area: 2.2 mg / cm 2 added to the electrolyte in a proportion of
[0098] According to the results, in the electrolytic capacitors of Examples 1 and 2 and Comparative Example 1, a carbon layer that breaks through the dielectric oxide film and is electrically conductive with the aluminum of the cathode foil is formed on the surface of the cathode foil, so it can be confirmed that the nitro compound uses the carbon layer as a reduction site to efficiently receive electrons and absorb hydrogen ions. On the other hand, in the electrolytic capacitor of Comparative Example 3, the surface of the cathode foil is covered with a dielectric oxide film, so it can be confirmed that the area where the nitro compound receives electrons is limited to the end face area of the cathode foil, and the absorption of hydrogen ions cannot keep up, and hydrogen gas continues to be generated.
[0099] As described above, the cathode body has a carbon layer as a reduction site on the surface, whereby the nitro compound efficiently receives electrons to promote the absorption reaction of hydrogen ions, thereby being able to suppress the generation of hydrogen gas.
[0100] Here, the cathode body of the electrolytic capacitor of Comparative Example 4 has a carbon layer, and no nitro compound is added to the electrolyte. The electrolytic capacitor of Comparative Example 4 begins to expand during the aging process during production, and the expansion becomes rapid after the measurement of the gas generation amount starts.
[0101] The cathode body of the electrolytic capacitor of Comparative Example 2 does not have a carbon layer, and the amount of nitro compound added to the electrolyte is 2 Projected area limited to 1.5 mg / cm 2The electrolytic capacitor of Comparative Example 2, which has no carbon layer and too little nitro compound added, also began to expand during the aging process during production, and expanded rapidly immediately after the measurement of the amount of gas generated was started.
[0102] In the electrolytic capacitor of Comparative Example 2, the surface of the cathode foil is covered with a dielectric oxide film, the region where the nitro compound receives electrons is limited to the end region of the cathode foil, and the amount of the nitro compound added is small. Therefore, in the electrolytic capacitor of Comparative Example 2, the opportunity for the reduction reaction of the nitro compound is limited, and it is presumed that the generation of hydrogen gas cannot be suppressed.
[0103] On the other hand, the electrolytic capacitor of Example 2 was added with the same amount of nitro compound as that of Comparative Example 2. However, it is believed that the nitro compound of Example 2 can obtain a large number of reduction reaction opportunities using the carbon layer as a reduction site. Therefore, it is believed that the nitro compound of Example 2 effectively suppresses the generation of hydrogen in the electrolytic capacitor using aluminum foil as a cathode body, although the amount of addition is too small.
[0104] According to these results, if the surface conditions of the cathode body are the same, the more the nitro compound is added to the electrolyte, the more the chance of the reduction reaction of the nitro compound continues, and the generation of hydrogen can be further suppressed. Therefore, it can be said that by adding a large amount of nitro compounds to the electrolyte, the generation of hydrogen can be further suppressed. In addition, the electrolytic capacitor using the cathode body with the reduction site is compared with the electrolytic capacitor using the cathode body without the reduction site, and it is confirmed that the addition of the nitro compound to the electrolyte is equal or less, and the generation of hydrogen can be efficiently suppressed. Therefore, it can be said that the cathode body formed with the reduction site can efficiently suppress the generation of hydrogen by the nitro compound.
[0105] (Electrostatic capacitance measurement test)
[0106] The electrostatic capacitance of the electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 and 3 was measured. A high voltage of DC450V was continuously applied to each electrolytic capacitor at a temperature of 105°C, and the electrostatic capacitance at each time was measured. An LCR meter (Agilent Technologies, 4284A) was used for the measurement. The measurement environment was an ambient temperature of 20°C, an AC voltage level of less than or equal to 0.5Vrms, and a measurement frequency of 120Hz.
[0107] The relationship between electrostatic capacitance and elapsed time is Figure 3 In addition, the relationship between electrostatic capacitance and accumulated charge is shown in Figure 4 Shown. Figure 3 It is a graph showing the temporal change of the electrostatic capacitance of Examples 1 and 2 and Comparative Examples 1 and 3. Figure 4This is a graph showing the electrostatic capacitance of Examples 1 and 2 and Comparative Examples 1 and 3 in units of accumulated electricity.
[0108] like Figure 3 and 4 As shown, the electrolytic capacitor of Comparative Example 3 has no significant capacitance change relative to the time elapsed and the accumulated amount of leakage current. On the other hand, the electrolytic capacitor of Comparative Example 1 has a significantly lower capacitance than Comparative Example 3 in the middle. In contrast, the electrolytic capacitors of Examples 1 and 2 remain unchanged relative to Comparative Example 3, and have no significant capacitance change relative to the time elapsed and the accumulated amount of leakage current.
[0109] Thus, in the case of a cathode body using a carbon layer having a reduction site for a nitro compound, it was found that when the amount of the nitro compound added was small, no capacity reduction was observed over time, but when the amount of the nitro compound added was large, a capacity reduction was observed over time. In other words, in the case of a cathode body using a carbon layer having a reduction site for a nitro compound, when the amount of the nitro compound added was small, no capacity reduction was observed regardless of the accumulated amount of electricity, but when the amount of the nitro compound added was large, a capacity reduction was observed by the accumulated amount of electricity.
[0110] On the other hand, in the case of using a cathode body in which a carbon layer as a reduction site for a nitro compound is not formed, it is found that even if a large amount of nitro compound is added, no decrease in capacity is confirmed over time. In other words, in the case of using a cathode body in which a carbon layer as a reduction site for a nitro compound is not formed, it is found that even if a large amount of nitro compound is added, no decrease in capacity is confirmed by the accumulated amount of electricity.
[0111] That is, it is suggested that the capacity reduction caused by the nitro compound is a phenomenon that occurs when a cathode body having a carbon layer as a reduction site of the nitro compound is used and when the electrolytic capacitor reaches a cumulative charge at which the capacity reduction occurs due to the addition of the nitro compound to the electrolyte, and when the nitro compound remains in the electrolyte. This indicates that in order to cause the reduction reaction of the nitro compound through the reduction site of the cathode body, thereby suppressing the generation of hydrogen gas and avoiding the capacity reduction caused by the nitro compound, it is necessary to limit the amount of nitro compound added to the electrolyte to an amount that will disappear before the electrolytic capacitor reaches a cumulative charge at which the capacity reduction phenomenon caused by the nitro compound occurs.
[0112] In the electrolytic capacitor of Comparative Example 1, the nitro compound is present in an amount of 1 cm2 per cathode body. 2 Projected area: 2.2 mg / cm 2In contrast, in the electrolytic capacitors of Examples 1 and 2, the nitro compound is added to the electrolyte at a maximum of 1 cm2 per 1 cm2 of the cathode body. 2 Projected area: 1.5 mg / cm 2 added to the electrolyte in a proportion of
[0113] In Comparative Example 1, the cathode body is doped with a large amount of nitro compound and has a carbon layer as a reduction site that increases the chance of reduction reaction of the nitro compound. Therefore, in Comparative Example 1, the reduction product of the nitro compound is estimated to be generated in an amount exceeding the allowable amount of the electrolytic capacitor of Comparative Example 1. In Comparative Example 1, the electrostatic capacitance is estimated to be reduced by the reduction product.
[0114] In contrast, in Examples 1 and 2, the cathode body has less carbon dioxide per 1 cm 2 Projected area less than or equal to 1.5 mg / cm 2 Therefore, in Examples 1 and 2, it is estimated that the reduction product of the nitro compound is less than the allowable amount of the electrolytic capacitor. In addition, in Examples 1 and 2, it is estimated that there is no obstruction to the discovery of electrostatic capacitance.
[0115] As described above, according to the gas generation measurement test and the electrostatic capacitance measurement test, the cathode body has a reduction site such as a carbon layer, and the cathode body has a reduction site such as a carbon layer. 2 Projected area less than or equal to 1.5 mg / cm 2 By adding the nitro compound in a ratio of , it was confirmed that the nitro compound can effectively suppress the generation of hydrogen without reducing the electrostatic capacitance of the electrolytic capacitor.
Claims
1. An electrolytic capacitor, characterized in that: have: an anode foil having a dielectric oxide film formed thereon; a cathode body having reduction sites on a surface; and The electrolyte, which is between the anode foil and the cathode body, contains a nitro compound, The cathode body comprises: a cathode foil composed of a valve metal; and A carbon layer, which is laminated on the cathode foil, becomes the reduction site, The nitro compound is present in an amount of 1 cm2 of the cathode body. 2 A proportion of the projected area less than or equal to 1.5 mg is contained in the electrolyte.
2. The electrolytic capacitor according to claim 1, characterized in that: The cathode foil has a cathode side expansion portion on the surface. The carbon layer is formed on the cathode-side expansion portion.
3. The electrolytic capacitor according to claim 2, characterized in that: The carbon layer and the cathode-side expanded portion are crimped.
4. The electrolytic capacitor according to claim 2, characterized in that: The carbon layer enters into the cathode side expansion portion.
5. The electrolytic capacitor according to claim 4, characterized in that: The cathode side expansion portion has sponge-like pits, The carbon layer comprises a carbon material, The carbon material of the carbon layer enters the sponge-like pits.
6. The electrolytic capacitor according to any one of claims 1 to 5, characterized in that: The anode foil has: an expanded portion formed on the surface of the foil; and A dielectric oxide film is formed on the surface of the expanded portion and has a thickness greater than or equal to 200 nm.
7. The electrolytic capacitor according to any one of claims 1 to 5, characterized in that: The anode foil has a value less than or equal to 3.5 μF / cm 2 of electrostatic capacitance.
8. The electrolytic capacitor according to any one of claims 1 to 5, characterized in that: It is used for medium and high voltage applications of 160V or more.
Citation Information
Patent Citations
Electrolyte for electrolytic capacitor
JP1992010512A